Analysis of Difficulties Learning Arabic For Class VII Students of Madrasah Tsanawiyah - Mujahidin Mujahidin (Sekolah Tinggi Agama Islam Al-Furqan, Makassar - Indonesia, 2024)
The aim of this research is to find and describe students' difficulties in learning Arabic. The method used in this research is a descriptive qualitative method or a qualitative approach. And to obtain data, researchers use data collection procedures by means of observation, interviews, documentation. The results of this research show that the Arabic language skills of class VII MTs Nurul Aziz DDI Barobbo can be said to be still not good, students still have difficulty learning Arabic, the first cause is when students cannot differentiate hijaiyyah letters which are almost the same in pronunciation, they are unable to read the Al-Qur'an. an, and their lack of motivation in learning Arabic, parents' lack of attention to students' Arabic learning outcomes, and no basic mastery of Arabic. There is a lack of seriousness in taking Arabic lessons and boredom arises when the teaching and learning process takes place. The teacher's method of delivering material is monotonous, using the lecture method, and the use of less varied learning media.